Non-cognitive differences between abacus-trained students and their counterparts. (June 2022) - Mou, Cong; Wei, Xiyu; Zhou, Xinlin
Abstract: While most empirical studies have concentrated on the association between abacus proficiency and cognitive abilities, there is far less research on abacus proficiency and non-cognitive characteristics. We propose a "relevance hypothesis" to explain the possible transfer of abacus training to non-cognitive development. It was predicted that abacus-skilled students would show advantages over untrained students in some non-cognitive characteristics. Participants were 68 abacus-skilled children and 73 untrained children aged 8–13 years old. All participants completed seven cognitive tests and seven self-reported questionnaires that assessed various non-cognitive constructs. Results showed that the abacus group demonstrated better mental rotation and arithmetic calculation performance. Notably, the abacus group also demonstrated higher perseverance, self-control, achievement motivation, and mathematics self-efficacy than the non-abacus-trained group. The current study is the first to explore improvements in non-cognitive characteristics associated with abacus training. Implications are discussed based on the relevancy between abacus training and non-cognitive characteristics within general educational contexts.